Meat Food Group Intakes and the Risk of Type 2 Diabetes Incidence - Hosseini-Esfahani, Firoozeh; Beheshti, Niloofar; Koochakpoor, Glareh; Mirmiran, Parvin; Azizi, Fereidoun (Frontiers in Nutrition, 2022)
Aim This study aimed to evaluate the association of meats and their substitute food group intakes, including nuts, eggs, and legumes, with type 2 diabetes (T2D). Methods For this secondary analysis, we selected eligible adults (n = 6,112) from the Tehran Lipid and Glucose Study participants with a median follow-up of 6.63 years. Expert nutritionists assessed dietary intakes using a valid and reliable semiquantitative food frequency questionnaire. Biochemical and anthropometric variables were assessed at baseline and follow-up examinations. We used multivariable Cox proportional hazard regression models to estimate the new onset of T2D concerning meats and their substitute food groups. Results We performed this study on 2,749 men and 3,363 women, aged 41.4 ± 14.2 and 39.1 ± 13.1 years, respectively. The number of participants with incident T2D was 549. After adjusting for confounders, legume [HR: 1, 0.74 (0.58–0.94), 0.69 (0.54–0.90), 0.65 (0.50–0.84), P-trend = 0.01)] was inversely associated with incident T2D. Fish intake [HR: 1, 1.0 (0.79–1.27), 1.17 (0.91–1.50), 1.14 (0.89–1.45), P-trend = 0.01)] was positively associated with incident T2D. In subjects who reported poultry consumption of 36.4–72.8 g/day, a positive association [HR: 1.33 (1.03–1.71)] between poultry intake and T2D risk was observed. Conclusion Our findings revealed that a diet rich in legumes significantly reduced the risk of T2D incidence, while a diet high in poultry increased the risk of T2D incidence, probably due to high-temperature cooking methods and environmental contaminants.